Are the widespread scatters of stone artefacts on dune surfaces in southeastern arid Australia really late Holocene in age?. Issue 1 (2nd January 2021) - Hughes, Philip; Mosig Way, Amy; Sullivan, Marjorie
Abstract: Vast numbers of stone artefact clusters (commonly called artefact scatters) occur on dune surfaces throughout southeastern arid Australia, virtually all of them undated. They were interpreted by researchers in the 1980s and 1990s as being mainly of late Holocene age on the basis of their surface or near-surface locations and the composition of their assemblages, which include backed artefacts, tulas and unifacial points. In this article, we analyse dated archaeological sites in the Roxby dunefield to test the reliability of this interpretation. Our analyses indicate that we can be confident that most of the artefacts in the many thousands of other recorded but undated sites in this dunefield are of late Holocene age. Throughout the region, the post-LGM geomorphic histories of dunes in relation to their archaeological records were broadly similar, allowing us to conclude that, on the balance of probabilities, earlier researchers working throughout the southeast arid zone were correct to conclude that the sites on the surfaces of these dunes were essentially late Holocene in age. Abbreviations: BA+T+UP: backed artefacts, tulas and unifacial points combined; ENSO: El Niño Southern Oscillation; LGM: last glacial maximum; OH&S: occupational health and safety